Where have all the livestock gone? - Bourn, D.M.; Denda, I.; Ridder, N.A. de; Wagenaar, K.T.; Wint, W. (International Livestock Centre for Africa, 1987)
Discusses, based on aerial surveys taken before and after the drought, the magnitude of population changes, both human & animal, that took place in west Central Niger during the drought and how the drought has affected different ethnic groups. Includes data on estimates of livestock population & pastoral dewellings.